2014
DOI: 10.1111/ahe.12098
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Anatomy of the Lower Respiratory System in Mole rats (Spalax leucodon)

Abstract: The morphologic and morphometric features of the lower respiratory system in mole rats were examined. It was seen that the low respiratory system of this species leading a special life under highly hypoxic/hypercapnic conditions underground is structurally similar to other mammals living on land in terms of the parts examined; trachea was formed by 29.5 ± 4 oval-formed cartilaginous tracheals arranged backwards and became gradually more stenotic diameter from cranial to the caudal of the neck. The trachea was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
1
22
0
2
Order By: Relevance
“…They also resembled those of surface-and underground dwelling rodents 114,115 . The undivided left lung of C. gambianus, which was also reported in the same rodent by Ibe et al 60 , and the existence of three lobes on the left lung of C. foxi are not unique morphological features: various permutations in the lobulations of the lung occur in the mammalian lungs 61,62,113,[116][117][118][119][120][121] . Ostensibly, there is no evidence showing that lobulation of the lung is of functional consequence [122][123][124][125][126][127][128][129][130][131][132][133][134] .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…They also resembled those of surface-and underground dwelling rodents 114,115 . The undivided left lung of C. gambianus, which was also reported in the same rodent by Ibe et al 60 , and the existence of three lobes on the left lung of C. foxi are not unique morphological features: various permutations in the lobulations of the lung occur in the mammalian lungs 61,62,113,[116][117][118][119][120][121] . Ostensibly, there is no evidence showing that lobulation of the lung is of functional consequence [122][123][124][125][126][127][128][129][130][131][132][133][134] .…”
Section: Discussionsupporting
confidence: 55%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ woodlands and rocky places in colonies which excavate extensive burrows 111,112 . While gross anatomical and histological details on the structure of the respiratory system of C. gambianus exist 60,113 , C. foxi has not hitherto been investigated. Here, it was observed that while the lobulation of the lungs of the two species differed markedly, at histological-and ultrastructural levels, the organs were quite similar.…”
Section: Discussionmentioning
confidence: 99%
“…This number is similar to the European Hamster which had 14 rings (Reznik, Reznik‐Shuller, & Mohr, ). However, They differ from other rodents like mole rats that showed 29 rings (Ilgun, Yoldas, Kuru, & Özkan, ) and the capybara who presented 43 tracheal rings (Moreto, Oliveira, Bertassoli, & Neto, ). Hare () describes that the tracheal rings of mammals vary from 29 to 60, differing of our results.…”
Section: Discussionmentioning
confidence: 61%
“…O padrão de pulmão direito dividido em quatro lobos e o esquerdo em dois diferiu apenas do descrito em toupeiras por Ilgun et al (2014), nas quais o pulmão esquerdo não apresenta nenhuma divisão em lobos.…”
Section: Discussionunclassified